2021
DOI: 10.1002/ppul.25422
|View full text |Cite
|
Sign up to set email alerts
|

Is viral coinfection a risk factor for severe lower respiratory tract infection? A retrospective observational study

Abstract: Objective To determine whether viral coinfection is a risk for severe lower respiratory tract infection (LRTI). Working Hypothesis Children with viral coinfection had a higher risk for admission to the intensive care unit (ICU) than those with a single virus infection. Study Design Retrospective, observational study for 10 years. Patient‐Subject Selection Children between 1 and 60 months of age hospitalized with LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…In our review, 27 of the included studies reported risk factors for poor outcomes among children with RSV-associated ALRI, 17,22–47 2 studies reported data for influenza, 48,49 and 1 study for SARS-CoV-2. 50 Therefore, we only carried out meta-analysis and subgroup analysis for RSV-associated ALRI.…”
Section: Resultsmentioning
confidence: 99%
“…In our review, 27 of the included studies reported risk factors for poor outcomes among children with RSV-associated ALRI, 17,22–47 2 studies reported data for influenza, 48,49 and 1 study for SARS-CoV-2. 50 Therefore, we only carried out meta-analysis and subgroup analysis for RSV-associated ALRI.…”
Section: Resultsmentioning
confidence: 99%
“…La coinfección viral respiratoria aguda requiere una mayor atención y más recursos por parte del personal sanitario, a consecuencia de la sintomatología, el tratamiento y pronóstico se verán afectados dependiendo el patógeno que coinfecta al ser humano. https://doi.org/10.56294/saludcyt2024634 5 Pérez V, et al CONCLUSIONES La presente revisión sistemática proporciona evidencia sobre la presencia de coinfecciones respiratorias virales en pacientes SARS COV-2 positivos, a pesar de que la incidencia de COVID-19 sigue siendo alta, la prevalencia de coinfecciones virales respiratorias es relativamente baja. Las medidas de control de infecciones a nivel mundial pueden haber contribuido a reducir la circulación de virus respiratorios.…”
Section: Discussionunclassified
“…(1) Los virus más prevalentes son el virus de influenza tipo A y B, virus respiratorio sincitial (VRS), rinovirus(HRV), adenovirus y coronavirus, (2,3,4) en niños se han detectado más comúnmente VRS y HRV, seguido de coronavirus. (5,6,7) En Ecuador la enfermedad respiratoria más frecuente es la neumonía, cuyo agente causal primordial es el VRS. (8) Desde el 2019 con la aparición de una nueva variante de coronavirus, COVID-19 (SARS-CoV-2), declarada como pandemia el 11 de marzo del 2020 por la Organización Mundial de la Salud (OMS) por su rápida propagación, ha provocado millones de contagios y muertes en cualquier grupo etario, (9) en Ecuador se registraron 1 067 327 personas confirmadas de coronavirus y 36 034 personas fallecidas.…”
Section: Introductionunclassified
“…28 In another study conducted in Türkiye again, RSV (42.8%), HRV (34.7%), and HBoV (10.0%) were detected in children less than 5 years of age with severe LRTIs. 29 ARDS developed in 28.6% of the patients hospitalized in the PICU with a diagnosis of viral LRTI, and it was the most common complication among the patients hospitalized with viral infection. 30 In our study, the ratio of ARDS development was 9.4% in PCR-positive patients hospitalized in PICU with LRTIs.…”
Section: Discussionmentioning
confidence: 99%